Aetiology and outcome in 53 cases of native valve staphylococcal endocarditis. Issue 887 (1st September 1999) - Hricak, V; Kovacik, J; Marks, P; West, D; Kromery, V
Abstract : Within the last 30 years the profile of infective endocarditis has altered considerably with regard to microbiological causation, clinical features, and natural history. A contributory factor has undoubtedly been the development of potent antibiotics and their sometimes indiscriminate use. The increase in intravenous drug abuse in urban centres, the use of immunosuppressive agents, and the use of prosthetic heart valves have also all contributed. Although cardiac surgery in the uninfected heart provides a perfect environment for infective endocarditis, the improved design of prosthetic valves and the enhanced long-term survival and decreased immediate operative risk, means that surgery is viewed as the best option in many cases. In a series of 53 cases of staphylococcal endocarditis from a national endocarditis survey, those risk factors which influenced outcome were analysed. Thirty out of 53 patients had predisposing heart disease. Mortality was 39.6%. Statistical analysis revealed that attributable mortality was significantly associated with skin infection, systemic embolisation, and inappropriate therapy. Interestingly, surgical treatment was associated with better outcome.